The role of p53, PCNA and Ki-67 as outcome predictors in the treatment of laryngeal cancer - Sarafoleanu, D; Postelnicu, V; Iosif, C; Manea, C; Sarafoleanu, C (Journal of medicine and life, 2009)
The aim of our study was to determine the importance of p53, PCNA and Ki-67, evaluated by immunohistochemistry, in the treatment and prediction of the laryngeal carcinoma. Out of a total of 319 patients with laryngeal carcinoma that underwent surgery in our department between 1999 and 2007, we performed a retrospective study on 71 cases who benefited by immunohistochemical guidance before the beginning of the treatment. All these patients have been followed-up two to five years after surgery. The values of p53, PCNA and Ki-67 are strongly correlated with the histological grading, by means of descriptive statistics (confidence level 95%); the mean values of these three markers corresponding to each HP grade. A highly statistical significant positive correlation (r = 0.84, p < 0.001 ) between the values of p53 and PCNA was observed. The values of p53, PCNA and Ki-67 in the patients from this study are strongly correlated with the absence of the loco-regional lymph node metastases, by means of descriptive statistics (confidence level 95%). Ki-67 only is correlated significantly to the presence of lymphatic metastases in the regional lymph nodes (stage N1, N2 or N3 TNM). P53 and PCNA are not correlated significantly with the presence of the metastases in the regional lymph nodes.